Spatial analysis of drought-prone locations using geographic information systems in Hulu Sungai Utara Regency - Ridha, Haji Muhammad; Mahmud, Mahmud (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2026)
Hulu Sungai Utara Regency is one of the regions in South Kalimantan Province that has a high potential for drought disasters due to the influence of climate variability, the relatively flat physical condition of the region, and limited spatial information regarding drought-prone areas. The absence of accurate vulnerability maps has resulted in mitigation efforts not being optimal. This study aims to map the level of drought vulnerability in Hulu Sungai Utara Regency and identify the main factors that influence it. The method used is a Geographic Information System (GIS)-based spatial analysis with a weighted overlay technique using the Analytical Hierarchy Process (AHP) method. The parameters analyzed include slope gradient, land elevation, rainfall, soil type, land cover, river density, vegetation index (NDVI), wetness index (NDWI), and land surface temperature (LST). The results show that most areas of Hulu Sungai Utara Regency are categorized as moderately drought-prone with a percentage of 95.361%, while the non-vulnerable category only covers 4.639% of the area, and no highly vulnerable areas were found. The most influential factor on drought vulnerability is rainfall, followed by NDWI and NDVI. It is hoped that the resulting vulnerability map can be the basis for mitigation planning and sustainable water resource management.